HECT ubiquitin ligases as accessory proteins of the plant proteasome. Issue 2 (5th August 2022) - Wang, Zhishuo; Spoel, Steven H.
Abstract: The proteasome plays vital roles in eukaryotic cells by orchestrating the regulated degradation of large repertoires of substrates involved in numerous biological processes. Proteasome dysfunction is associated with a wide variety of human pathologies and in plants severely affects growth, development and responses to stress. The activity of E3 ubiquitin ligases marks proteins fated for degradation with chains of the post-translational modifier, ubiquitin. Proteasomal processing of ubiquitinated substrates involves ubiquitin chain recognition, deubiquitination, ATP-mediated unfolding and translocation, and proteolytic digestion. This complex series of steps is made possible not only by the many specialised subunits of the 1.5 MDa proteasome complex but also by a range of accessory proteins that are recruited to the proteasome. A surprising class of accessory proteins are members of the HECT-type family of ubiquitin ligases that utilise a unique mechanism for post-translational attachment of ubiquitin to their substrates. So why do proteasomes that already contain all the necessary machinery to recognise ubiquitinated substrates, harbour HECT ligase activity? It is now clear that some ubiquitin ligases physically relay their substrates to proteasome-associated HECT ligases, which prevent substrate stalling at the proteasome. Moreover, HECT ligases ubiquitinate proteasome subunits, thereby modifying the proteasome's ability to recognise substrates. They may therefore enable proteasomes to be both non-specific and extraordinarily selective in a complex substrate environment. Understanding the relationship between the proteasome and accessory HECT ligases will reveal how the proteasome controls so many diverse plant developmental and stress responses.